2014
DOI: 10.1063/1.4891684
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxygen doping in microcrystalline SiGe p-i-n solar cells

Abstract: The effect of doping with oxygen the microcrystalline silicon-germanium absorber layer of single-junction p-i-n solar cells has been studied. In parallel, the absorber layer quality was measured by depositing absorber layers directly on glass and measuring their electrical properties. By doping the absorber layer with the optimum oxygen concentration (about 1.4×1019 cm−3), an increase in short-circuit current density of almost 4 mA/cm2 was achieved in 3 μm thick p-i-n solar cell. This effect is attributed to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…It has been reported that the higher stabilized efficiency of the solar cells prepared by triode PECVD originates mainly from the improved stabilized FF, in comparison with our standard solar cells prepared by diode PECVD. 16) From the sub-bandgap absorption measurement by Fourier transform photocurrent spectroscopy 17,[23][24][25][26] on light-soaked p-i-n devices, we observed that absorption at photon energies of <1.5 eV is lower for the solar cell prepared by triode than that by diode PECVD. The lower sub-bandgap absorption reflects the higher FF, indicating that the light-induced degradation of a-Si:H solar cell is primarily governed by the amount of metastable defects in the absorber layer.…”
Section: Single-junction Solar Cellsmentioning
confidence: 94%
“…It has been reported that the higher stabilized efficiency of the solar cells prepared by triode PECVD originates mainly from the improved stabilized FF, in comparison with our standard solar cells prepared by diode PECVD. 16) From the sub-bandgap absorption measurement by Fourier transform photocurrent spectroscopy 17,[23][24][25][26] on light-soaked p-i-n devices, we observed that absorption at photon energies of <1.5 eV is lower for the solar cell prepared by triode than that by diode PECVD. The lower sub-bandgap absorption reflects the higher FF, indicating that the light-induced degradation of a-Si:H solar cell is primarily governed by the amount of metastable defects in the absorber layer.…”
Section: Single-junction Solar Cellsmentioning
confidence: 94%
“…These properties have opened a way of using Si 1−x Ge x to manufacture different electronic devices: high-speed transistors, 1 long-wave infrared detectors, 2 solar cells based on p-i-n structures. 3 The use of silicon and germanium in optoelectronics is limited by the fundamental feature of their indirect band structure: the extrema of the conduction band are near the edge of the Brillouin zone, and the top of the valenceband is at the center of this zone. However, in nanocrystals (NCs), electrons and holes are localized and no longer have a definite (quasi)momentum due to the Heisenberg uncertainty principle.…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of Si 1−x Ge x material is high mobility and convenient, well-developed production technology. These properties have opened a way of using Si 1−x Ge x to manufacture different electronic devices: high-speed transistors [1], long-wave infrared detectors [2], solar cells based on SiGe p-i-n structures [3].…”
Section: Introductionmentioning
confidence: 99%
“…And, they attributed this effect to the oxygen doping compensating for the space charges caused by the germanium dangling bounds rather than the direct defect passivation. [13] In their experiment, the oxygen doping of the i-layer was conducted by using 1% CO 2 diluted in H 2 , because the required gas flow is so small that a diluted gas must be used. During crysctalization of µc-SiGe, oxygen impurities adsorb onto the surfaces or grain boundaries (i.e., surface doping, including the occupation of surface vacancy or replacement of surface atom), and then diffuse into bulk (i.e., bulk doping, including occupation of inner vacancy or replacement of host atom).…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the experimental work in Ref. [13], we believe that it is necessary to systematically study the relationship between electronic structure and photovoltaic performance of O-doped µc-SiGe, in order to develop efficient µc-SiGe-based solar cells. Thus, in the present work, the crystal structure and electronic structure of O-doped SiGe are investigated by using density functional theory (DFT) calculations.…”
Section: Introductionmentioning
confidence: 99%